The Effect of Zeolite Imidazole Framework Geometrical Structure on Carbon Dioxide Permeability for Mixed Matrix Membrane - Najdi, Nurhani Nadiah Mohd; Shafie, Siti Nur Alwani; Nordin, Nik Abdul Hadi Md; Yusoff, Norhaniza; Othman, Mohd Hafiz Dzharfan (ASEAN Journal for Science and Engineering in Materials, 2022)
As the trade-off limitation of polymeric membrane between permeability and selectivity is still the biggest concern, the focus has now diverted into the potential of Mixed Matrix Membrane (MMM). Among the fillers used in MMM, the Zeolitic imidazole framework (ZIF) is one of the metal-organic frameworks (MOF) currently being investigated where findings have shown outstanding performances. Thus, this study aims to investigate the effect of fillers geometry on MMM’s gas separation performance. The successful synthesis of ZIF-8 and ZIF-L were confirmed using X-Ray Diffraction (XRD) to measure the crystallinity, Scanning Electron Microscopy (SEM) to observe structure and morphology, and Fourier Transform Infrared (FTIR) to assess the functional groups of the ZIF-L and ZIF-8 particles. The gas permeation test shows that at the highest filler loading of 10wt%, ZIF-L MMM gives higher CO¬2 permeability (271 GPU) as compared to ZIF-8 MMM (121 GPU).